2014
DOI: 10.1016/j.jssc.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical delithiation and exfoliation ofLixCoO2

Abstract: Progressive chemical .delithiation of commercially available lithium cobalt oxide (LiCoO2) showed consecutive changes in the crystal properties. Rietveld refinement of high resolution X-ray and neutron diffraction revealed an increased lattice parameter c and a reduced lattice parameter a for chemically delithiated samples. Using electron microscopy we have also followed the changes in the texture of the samples towards what we have found is a critical layer stoichiometry of about LixCoO2 with x=1/3 that cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 34 publications
2
17
1
Order By: Relevance
“…Using equivalent treatment conditions to Basch and Kim (more detail in Supporting Information), our results were compiled with data from these reports. Our data demonstrate, by incorporating the loss of cobalt (54%), as determined from UV-Vis studies, with the Li:Co ratio determined by ICP-OES, that the total lithium loss is 82%, as opposed to 66% and 74% reported by Basch et al 59 Utilizing reported results of lithium occupancy after acid treatment as determined from neutron diffraction, 37 at.% Li is expected to remain in the structure. 59 .…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Using equivalent treatment conditions to Basch and Kim (more detail in Supporting Information), our results were compiled with data from these reports. Our data demonstrate, by incorporating the loss of cobalt (54%), as determined from UV-Vis studies, with the Li:Co ratio determined by ICP-OES, that the total lithium loss is 82%, as opposed to 66% and 74% reported by Basch et al 59 Utilizing reported results of lithium occupancy after acid treatment as determined from neutron diffraction, 37 at.% Li is expected to remain in the structure. 59 .…”
Section: Resultssupporting
confidence: 57%
“…Our data demonstrate, by incorporating the loss of cobalt (54%), as determined from UV-Vis studies, with the Li:Co ratio determined by ICP-OES, that the total lithium loss is 82%, as opposed to 66% and 74% reported by Basch et al 59 Utilizing reported results of lithium occupancy after acid treatment as determined from neutron diffraction, 37 at.% Li is expected to remain in the structure. 59 . When comparing to that of previously reported chemical compositions, such as Kim, Basch, and Takahashi this structure varies with the additional consideration of cobalt vacancies and oxygen valence compensation.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…At the same time, the Li ions could also be replaced by protons via ion-exchange, resulting in M(O,OH) 6 octahedra in the MO 2 layers, like the formation of Ni(O,OH) 6 in the case of acid leaching of LiNiO 2 . 23…”
Section: Validation Of the Mechanismmentioning
confidence: 99%